PIDANA MATI BERSYARAT DALAM KUHP 2023: ANALISIS POTENCIAL RECIDIVISME PADA KEJAHATAN KELAS BERAT NARKOTIKA - Maghfiroh, Lailil Jannah; Mahardhika, Vita (Universitas Islam Kadiri, 2026)
This study analyzes the normative regulation of the conditional death penalty under Law Number 1 of 2023 on the Criminal Code (KUHP 2023), its inconsistencies with Law Number 35 of 2009 on Narcotics, and the potential for recidivism among serious narcotics offenders as a criminological problem that must be accommodated within the conditional death penalty mechanism. Using normative legal research with statutory, conceptual, and comparative approaches including a comparative analysis with Singapore’s narcotics criminal law system. The findings reveal that the normative construction of the conditional death penalty in KUHP 2023 contains structural weaknesses due to the absence of standardized behavioral assessment parameters for convicts. At the same time, it generates normative inconsistencies with the Narcotics Law across philosophical, legal-principle, institutional, and technical dimensions. From a criminological perspective, serious narcotics offenders exhibit very high recidivism rates and systematically documented phenomena of controlling criminal networks from within correctional institutions. Consequently, the conditional death penalty mechanism is vulnerable to exploitation without evidence-based recidivism risk assessment instruments and adequate penitentiary infrastructure.